Kemampuan Tumbuhan Kayu Apu (Pistia stratiotes) dan Eceng Gondok (Eichhornia crassipes) Dalam Menurunkan Kadar Amoniak Pada Limbah Budidaya Ikan Lele Sangkuriang (Clarias gariepinus Var) - Evatu Silviana Caesari Putri; Ratna Djuniwati Lisminingsih; Husain Latuconsina (Jurnal Riset Perikanan dan Kelautan, 2022)
North African Catfish (Clarias gariepinus Var) is a new strain of catfish resulting from genetic engineering through back-crossing which is the most widely cultivated by the community. If aquaculture activities are not managed properly, it has the potential to pollute the aquatic environment through the input of aquaculture waste. Aquaculture waste water contains ammonia which can cause a decrease in water quality. This study aims to determine the ability of Water Lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes) as phytoremediation agents in the waste of Clarias gariepinus farming which contains ammonia. This study used a completely randomized design (CRD). It consisted of 5 treatments with 3 replications, as treatment P0 (control), P1 (45 gram wet weight), P2 (135 gram wet weight), P3 (45 gram wet water hyacinth), and P4 (water hyacinth wet weight 135 grams). Data were analyzed descriptively by looking at the morphological appearance of water hyacinth and water hyacinth on all treatments during the observation. The results of the study showed that water hyacinth and water lily plants were effective as phytoremediation agents because of their ability to reduce ammonia levels.